Fluoroscopically Guided Facet Injections: Comparison of Intra-Articular and Periarticular Steroid and Anesthetic Injection on Immediate and Short-Term Pain Relief - Kershen, L.M.; Nacey, N.C.; Patrie, J.T.; Fox, M.G. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: The effectiveness of facet injections is unclear in the literature. Our objective was to determine the immediate and short-term efficacy of intra-articular and periarticular steroid/anesthetic injections for facet-mediated lumbar pain.MATERIALS AND METHODS: All outpatient fluoroscopically guided facet injections at a single institution during a 54-month period were retrospectively and independently reviewed by 2 musculoskeletal (MSK) trained radiologists. All intra-articular, all periarticular, and partial intra-/periarticular injection locations were determined. Periarticular and partial peri-/intra-articular injections were combined for analysis. Preinjection, immediate, and 1-week postinjection numeric pain scores, patient age, sex, anesthetic/steroid mixture, fluoroscopic time, and physician performing the procedure were recorded.RESULTS: Seventy-seven patients (mean age, 51.1 years) had 100 procedures with 205 total facet joints injected. All intra-articular, all periarticular, and partial peri-/intra-articular injections constituted 54%, 20%, and 26% of the cases, respectively. The immediate and 1-week postprocedural change in pain was −3.7 (95% CI, −4.5 to −2.8; P < .001) and −1.4 (95% CI, −2.2 to −0.6; P = .001) for the all intra-articular and −3.6 (95% CI, −4.4 to −2.9; P < .001) and −1.2 (95% CI, −1.9 to −0.4; P = .002) for the combined group. Changes in immediate pain were significantly associated with the prepain level (P < .001) and patient age (P = .024) but not with the anesthetic used. Analyses revealed no significant difference in pain reduction between the groups either immediately or 1 week postinjection. Intra-articular injections required less fluoroscopic time (geometric mean, 39 versus 52 seconds) (P = .005).CONCLUSIONS: Intra-articular and periarticular fluoroscopically guided facet injections provide statistically significant and similar pain relief both immediately and 1 week postinjection.